Quality Management Practices in Namibian SMEs: An Empirical Investigation. Issue 2 (April 2021) - Mutingi, Michael; Chakraborty, Ayon
Small and medium enterprises (SMEs) have significantly contributed to growth, innovation and success of several economies across the world. However, SMEs in emerging economies have faced stiff competition in the global market. The purpose of this research is to provide an insight into the status of quality management (QM) practices in Namibian SMEs. This article presents a survey-based approach to evaluate the application of QM practices, the associated critical success factors (CSFs), business performance indicators for quality improvement and the reasons for non-implementation of the quality tools from an emerging economy perspective. An online questionnaire was designed and distributed to 182 Namibian SMEs through stratified random sampling. The overall response rate was 37.86 per cent. Analysis of results showed that the level of application of QM practices was generally low. The main reasons for not implementing QM initiatives were as follows: (a) unknown tools in enterprises, (b) difficulties in data collection and (c) high costs of training. Relative influences of CSFs and the Critical-to-Quality (CTQs) were also evaluated. Intriguingly, top management commitment and support was not a major CSF. Low response rate and context specificity tend to limit the generalization of the results. The study provides insights for policymakers to develop effective policies for QM education and training programmes, hence facilitating effective adoption of QM practices in a developing world context.